AB0029 Preliminary results on functional analysis of a card15/nod2 mutation (P.E383K) in patients with BLAU syndrome. (23rd January 2014) - Galozzi, P.; Greco, E.; Gava, A.; Sfriso, P.; Basso, D.; Plebani, M.; Punzi, L.
Abstract : Background: Blau syndrome (BS) is a rare, autosomal dominant autoinflammatory disease, characterized by granulomatous dermatitis, symmetrical arthritis and recurrent uveitis. The caspase recruitment domain gene CARD15/NOD2 has been identified as responsible for BS (1). To date, 11 BS-associated mutations have been identified. Few functional data on p.E383K mutation are available in literature, whereas p.R334W/Q is the most frequent and studied mutations. Several in vitro observations have reported an elevated basal NF-κB activity and a "gain of function" hypothesis has been proposed (2), suggesting a spontaneous release of inflammatory cytokines from BS patients. Objectives: We aimed at studying the functional profile of CARD15/NOD2 in patients carrying p.E383K mutation compared to healthy controls; in particular we focused on the cytokine levels since there is no evidence in literature. Methods: IL-1β, IL-6, IL-8 and TNF-α releases were measured by ELISA assays in peripheral blood mononuclear cells (PBMC) obtained from 3 patients with p.E383K mutation (3). All patients were members of the only one Italian affected family. Cells were cultured in vitro either with or without stimulation of muramyldipeptide (MDP, NOD2 agonist), lipopolysaccaride (LPS, a TLR-4 agonist) or a combination of MDP and LPS. Statistical comparisons were made between the means of patients and controls data, using multiple comparison with Fisher post hoc analysis. Results: In absence of stimulation, no differences in cytokine levels were detected in PBMC of both controls and patients. Interestingly, stimulation with LPS or MDP did not induce augmented production of each cytokine in PBMC from patients compared with those from controls; besides, the cytokine levels in patients appeared to be attenuated compared with the control group. Both in patients and controls, there were no statistically significant differences in each cytokine release comparing LPS or MDP stimuli and no stimulation, except for IL-8 (p=0.011 and p=0.045, after LPS stimulation in patients and in controls respectively). Notably, the synergistic stimulatory effect of the combination of MDP and LPS is observed for each cytokine only in control group (IL-1β, p=0.027; IL-6, p=0.001 and IL-8, p=0.002 referred to MDP; TNF-α, p=0.000 and 0.04 referred to MDP and LPS respectively). Conclusions: Our findings for p.E383K mutation correlate with those reported in literature for patients carrying p.R334W/Q mutations (4), showing a similar cytokine profile of BS patients for whichever mutations. Moreover, according to our data, it would seem not to exist a primarily mediation of IL-1β in Blau syndrome. More repeated measures should be made in order to justify our results for all cytokines. References: Miceli-Richard C et al. CARD15 mutations in Blau syndrome. Nat Genet 2001;29:19-20. Chamaillard M et al. Gene-environment interaction modulated by allelic heterogeneity in inflammatory diseases. Proc Natl Acad Sci USA 2004;100:3455-60. Van Duist MM et al. A new CARD 15 mutation in Blau syndrome. Eur J Hum Gen. 2005;13:742-7. TM et al. The NOD2 defect in Blau syndrome does not result in excess interleukin-1 activity. Arthritis Rheum. 2009;60:611-8. Disclosure of Interest: None Declared